Assessment of worklife areas and stress intensity among Border Guard officers - Agata Chudzicka-Czupała; Marta Stasiła-Sieradzka; Małgorzata Dobrowolska; Agnieszka Kułakowska (Nofer Institute of Occupational Medicine, 2018)
Background Stress is associated with the performance of high-risk occupations. It can be defined as a set of reactions that results from mismatched working conditions and requirements to capabilities of an employee. People who differently assess these areas of work may experience varying degrees of stress. Material and Methods The total of 128 Border Guard officers took part in the test. A subjective assessment of areas of work was made by using the Areas of Worklife Survey. The Perceived Stress Scale (PSS-10) was used to examine the severity of stress. Results Three groups of examined people, differing significantly in the assessment of all areas of working life, were identified. Affiliation of the examined people to these groups explains 8% of the variability in the severity of stress. The results of the regression analysis allowed to consider the assessments of 3 areas of working life (control, rewards and workload) as important predicators of the severity of stress experienced by officers. The model turned out to be statistically significant, the variables included in the model explain 19% of the variability of the dependent variable. Conclusions The officers who assess the areas of working life differently, differ in terms of severity of the experienced stress. The severity of stress is significantly related to the ability to make independent decisions and to enjoy rewards. The stress experienced by Border Guard officers is mainly related to the assessment of the following areas of work: sense of control, rewards and workload. Med Pr 2018;69(2):199-210